2000
DOI: 10.5507/bp.2000.018
|View full text |Cite
|
Sign up to set email alerts
|

Early Renal Failure After Mesalazine (Case Report)

Abstract: An early onset of asymptomatic renal failure in a young man with ulcerative colitis treated with high-dose mesalazine is the subject of this case report. After mesalazine withdrawal, renal function was quickly restored. In contrast with published case reports, the onset of renal impairment occurred very early. Serum urea reached pathological values 27 days and serum creatinine 15 days after mesalazine treatment was started. The diagnosis of renal impairment was supported by urine analysis (both semi-quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…8,18,52,59,61,63,64,70,71,73,76 -80,93 Other authors have reported only partial improvement of renal function after drug withdrawal. 21,51,[53][54][55][56]68,69,72,74,75,77,81,82 Finally, although most case reports indicate reversibility after cessation of the drug, in some cases permanent clinical kidney dysfunction has been observed. 55,56,58,63,65,69,77,79 Thus, it has been calculated that Ϸ10% of the patients with 5-ASA nephrotoxicity will develop end-stage renal disease.…”
Section: Is Renal Impairment Due To 5-asa Treatment Reversible?mentioning
confidence: 99%
“…8,18,52,59,61,63,64,70,71,73,76 -80,93 Other authors have reported only partial improvement of renal function after drug withdrawal. 21,51,[53][54][55][56]68,69,72,74,75,77,81,82 Finally, although most case reports indicate reversibility after cessation of the drug, in some cases permanent clinical kidney dysfunction has been observed. 55,56,58,63,65,69,77,79 Thus, it has been calculated that Ϸ10% of the patients with 5-ASA nephrotoxicity will develop end-stage renal disease.…”
Section: Is Renal Impairment Due To 5-asa Treatment Reversible?mentioning
confidence: 99%
“…The onset of renal impairment in IBD patients on 5-ASAs can vary widely, with reports highlighting its onset within 29 days and beyond 5 years 2 10 11. Several studies have confirmed that 50% of cases present within 1 year of treatment initiation 3 12.…”
Section: Introductionmentioning
confidence: 99%